2008
DOI: 10.1007/s11199-008-9418-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Psychological Distress Among Latin American Immigrants to the Canary Islands

Abstract: We compared gender differences in rates and correlates of psychological distress among Latin American immigrants to the Canary Islands, Spain. Immigrant men (n=150) and women (n=150) completed questionnaires about demographic and migration characteristics, immigration demands, and psychological distress. Women reported more distress and immigration demands related to loss and occupation than men. For women, not being employed full time and immigration demands related to loss, novelty, occupation, and language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…Table 3 presents bivariate associations controlling for gender, given the welldocumented importance of gender in immigration research (Aroian et al 2008;Donato et al 2008;Hansen, 2008). The demographic variables include gender and age at the time of the survey.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 presents bivariate associations controlling for gender, given the welldocumented importance of gender in immigration research (Aroian et al 2008;Donato et al 2008;Hansen, 2008). The demographic variables include gender and age at the time of the survey.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the literature has reported all of the dimensions of immigration stress considered in this study to affect both male and female Latino immigrants and other immigrant groups (e.g., Aorian, Norris, et al, 2008;Caetano et al, 2007;Goodkind et al, 2008;Revollo et al, 2011) and that results have been inconsistent in previous studies (e.g., Aroian,818 FALConIeR et AL. Kaskiri, et al, 2008;Aroian, Norris, et al, 2008), no specific hypotheses are formulated for each immigration stress dimension.…”
mentioning
confidence: 76%
“…ty in both men and women but with loss, occupation, and language difficulties only in women and not feeling at home only in men (Aorian, Norris, et al, 2008). Interestingly, even though this is the only study that has examined different dimensions of immigration stress in a Latino immigrant population, these immigrants were living in the Canary Islands, Spain, a country whose similarities in values and language to Latin American countries limits the possibilities of extending the findings of that study to Latino immigrants living in the U.S.…”
mentioning
confidence: 98%
“…In view of the common contention in the literature regarding women's sensitivity to the emotional effects of migration (Aroian et al, 2003;Magdol, 2000), a question arises as to the emotional well-being of the two types of women we studied. As indicated throughout the study, the interviews of the Independent Decision Makers revealed these young women to be in a state of exuberance throughout their transition.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction patterns of the Family Emissaries are in accordance with research findings on the strong impact of migration on the emotional well-being of women. These studies maintain that residential mobility is likely to disrupt social relations, which are more central to the basic well-being and functioning of women than of men (Aroian et al, 2003;Gilligan, 1982;Magdol, 2002 …”
Section: Migration and Its Characteristicsmentioning
confidence: 99%